Jamaica's Farm Credibly makes farming profitable with blockchain technology. - Baker, Varun (Technical Centre for Agricultural and Rural Cooperation, 2019)
Varun Baker, CEO of Develop Digitally (Jamaica) shares how his initiative, Farm Credibly , is helping farmers through the use of blockchain technology.